2022
DOI: 10.1029/2021je007021
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Ancient Fluvial Systems in Memnonia Sulci, Mars: Impact Crater Damming, Aggradation, and a Large Water Body on the Dichotomy?

Abstract: The geologic record of Mars points to an early history strongly influenced by aqueous processes. This record includes degraded impacts craters, consistent with fluvial erosion (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…For fan‐shaped deposits along the Mars dichotomy boundary, these different formation scenarios evoke dramatically different water volumes. Studies interpreting these deposits as deltas have suggested that they debouched into paleolake basins (Davis et al., 2022; Rivera‐Hernández & Palucis, 2019) or a hemisphere‐spanning ocean (De Toffoli et al., 2021). Questions remain, however, for the origin of the largest fan‐shaped deposit along the dichotomy boundary, located at the terminus of Hypanis Valles near the Chryse escarpment (11.2° N, 45.5° W; Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…For fan‐shaped deposits along the Mars dichotomy boundary, these different formation scenarios evoke dramatically different water volumes. Studies interpreting these deposits as deltas have suggested that they debouched into paleolake basins (Davis et al., 2022; Rivera‐Hernández & Palucis, 2019) or a hemisphere‐spanning ocean (De Toffoli et al., 2021). Questions remain, however, for the origin of the largest fan‐shaped deposit along the dichotomy boundary, located at the terminus of Hypanis Valles near the Chryse escarpment (11.2° N, 45.5° W; Figure 1a).…”
Section: Introductionmentioning
confidence: 99%